ANALISIS NILAI-NILAI PERJUANGAN DALAM NOVEL MELANGKAH KARYA J.S KHAIREN - Soulisa, Irwan (SOSCIED, 2024)
This study is entitled Analysis of Struggle Values ​​in the Novel Melangkah by J.S Khairen. The purpose of this study is to determine the values ​​of struggle in the novel Melangkah by J.S Khairen?. This study is a qualitative descriptive. The method used is a descriptive method. The data source is the Novel Melangkah by J.S Khairen and from the internet. The data collection technique using the reading technique is done by reading carefully and thoroughly the main data source of the study and . The novel reader is done carefully from the beginning to the end of the story and is done repeatedly and the author notes important things in the novel that relate to the values ​​of struggle in the novel. The data analysis technique used includes three components, namely data reduction, data presentation, and drawing conclusions. The research procedure carried out consists of several stages, namely data collection, data selection, analyzing selected data, and making a research report. The data validity technique uses theory triangulation, method triangulation, data source triangulation. Based on the research results, it can be concluded: The results of the research on the novel Melangkah by J.S Khairen, show Based on the research results on the values ​​of struggle contained in the novel Melangkah by J.S Khairen, as explained, it can be concluded as follows. (1) The value of being willing to sacrifice has 8 values, (2) The value of unity has 5 values, (3) The value of caring has 10 values, (4) The value of responsibility has 10 values, (5) The value of respect has 7 values, (6) The value of hard work has 10